Experimental Study on Increasing the Received Power of Antenna using Circularly-Polarized Array Antenna - A. Adya Pramudita; Lydia Sari; V. Windha Mahyastuti (Institute of Advanced Engineering and Science, 2012)
A method to increase the received power of an antenna system by combining polarization, space and frequency diversities is investigated in this paper. The antenna system under investigation consisted of an array of 10 microstrip antenna elements. Each antenna element is a microstrip antena with circular polarization. Two array antennas with circularly polarized elements have been designed for receiving eloctromagnetic energy in 900 MHz and 1800 MHz band. Laboratory measurement has been conducted to study the increase of antenna received power caused by combining space, polarizarion and frequency diversities. Results show that the proposed method is able to increase the received power by 12.9 dB at 900 MHz and by 8.4 dB at 1800 MHz in an indoor environment; and by 15.8 dB at 900 MHz and by 9.5 dB at 1800MHz. This increase is mainly contributed by the use of space diversity, namely the use of array of 10 elements which contributed to increase the received power by 10.3 dB in an indoor environment. The useof circularly-polarized element increased the received power by 2.6 dB. Of the three diversities proposed, frequency diversity was found to have the least significant contribution becase the received power from 1800 MHz band is smaller than the 900 MHz band.DOI:http://dx.doi.org/10.11591/ijece.v2i2.209